SELECTING THE MOST EFFECTIVE ELEMENTS OF THE MARKETING MIX AND THEIR ROLE IN INCREASING SALES VOLUME - A SURVEY STUDY IN THE GENERAL COMPANY FOR THE MANUFACTURE OF MEDICINES AND MEDICAL SUPPLIES IN SAMARRA - Researcher: Wtaban Abdullah Sayhud; Prof. Dr. Sami Dhiab Mahal (Scholars Digest Publishing, 2024)
This study aimed to analyze the impact of marketing mix elements (product, price, promotion, distribution) on sales volume in the General Pharmaceutical Company in Samarra city. The importance of the study lies in highlighting how to use marketing mix elements effectively to enhance sales and achieve success in a competitive business environment, especially in the pharmaceutical sector, which is characterized by the diversity of its products and strategic importance. A hypothetical study plan was adopted through which the study objectives and hypotheses were determined. The researcher used the descriptive analytical approach in order to reach the results, as data were collected using a questionnaire designed specifically for this purpose. (352) questionnaire forms were distributed to a sample of employees in the General Pharmaceutical Manufacturing Company. The study field was determined as the Samarra Pharmaceutical Laboratory, and the questionnaire forms were retrieved in full. The data were analyzed using a set of descriptive and analytical statistical methods, including the arithmetic mean, standard deviation, simple correlation coefficient, and simple linear regression coefficient, using SPSS version 27. The study reached several important results, the most prominent of which are: the existence of a statistically significant positive effect of each element of the marketing mix (product, price, promotion, distribution) on sales volume.
Keywords: Marketing mix, sales volume, pharmaceutical company.